Leaders’ Innovative Work Behavior: The Role of Business Acumen, Innovative Self-Efficacy, and Openness - Iswahyudi, Didik; Etikariena, Arum (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Based on the conservation of resources principle, behavior can be exhibited by an individual because of the resource investments that are deployed to obtain other resources. This study aims to examine the role of business acumen, innovative self-efficacy, and openness to experience, which are personal resources on innovative work behavior. The study involved leaders at PT X, an energy company in Indonesia (n = 232). The leaders were employees in senior management, middle management, or frontline management. Participants were selected using proportionate stratified sampling. Multiple regression analysis was used to test the research hypotheses. The study found that only business acumen (b = 0,22; p-value < 0,01) and openness to experience (b = 0.78; p-value < 0.01) can predict innovative work behavior. The results of this study provide alternative pathways for developing a more precise innovation-oriented leadership development program.